DETERMINASI EKONOMI PEMILIHAN KEBIJAKAN PENILAIAN PERSEDIAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2009-2012 - Afna Hasufa Faisyar, 10.05.52.0102; Suwarti, Titiek (Students Journal of Accounting and Banking, 2014)
To choose accountancy rules, firms are influenced by both microeconomic and macroeconomic situation. This research tries to observe some economic factors that may be can influence firms to choose accountancy rules in appraising theirinventory whether average method and/or First In First Out Method. This research is analyzed by using logistic regression. The factors tested in this research are the size of the firms, leverage, liquidity, and earning before taxes. Inview of the importance of accountants role in choosing inventory valuation method, so I add this factor in this research. The result of this research shows that the size of the firm proved significantly influences management to choose inventory valuation method while leverage, liquidity, earning before taxes, and accounting conservatism is not proved significantly influence management to choose inventory valuation method.Keywords: Inventory Valuation Method, leverage, liquidity, earning before taxes, accounting conservatism